Social media and law enforcement practice in Poland : insights into practice outside anglophone countries - Waszkiewicz, Paweł (Routledge, 2024)
"This book explores the role of social media in the daily practice of Polish criminal justice and how social media is, in turn, reshaping this practice. Based on empirical research, it confronts common beliefs about how police officers, prosecutors, and judges use social media in their work. Readers will find answers to questions such as Which social media platforms are popular among law enforcement officers in Poland? How do the police use social media to investigate and prosecute crimes? What are the strategies for using social media to communicate with the community? What strategies are most successful? The findings in this book challenge some popular beliefs and theories about social media in criminal justice. As the first book to explore the use of social media in criminal justice outside of English-speaking countries, this collection of academic research will be of interest to academics focusing on criminology, criminal justice, and policing, and will also be useful to police leaders and officers, police social media administrators, prosecutors, and judges who may be inspired by the research to implement new successful and more effective practices"-- Provided by publisher.
Keywords: Law enforcement -- Poland.; Social media -- Poland.; Criminal justice, Administration of -- Poland.; Lois -- Application -- Pologne.; Médias sociaux -- Pologne.; LAW / Criminal Law / General; SOCIAL SCIENCE / Criminology